2006
DOI: 10.1177/0734282905285225
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Stability of Membership in a Wechsler Intelligence Scale for Children–Third Edition (WISC-III) Subtest Core Profile Taxonomy

Abstract: Although often applied in practice, clinically based cognitive subtest profile analysis has failed to achieve empirical support. Nonlinear multivariate subtest profile analysis may have benefits over clinically based techniques, but the psychometric properties of these methods must be studied prior to their implementation and interpretation. The current study posed the following question: Is Wechsler Intelligence Scale for Children-Third Edition (WISC-III) cluster membership based on nonlinear multivariate sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Distinct cognitive profiles characterized by specific weaknesses (in broad-based cognitive processing, executive functioning, verbal functioning, or nonverbal-visuospatial processing) were reported in previous cluster-analytic studies on the Wechsler Intelligence Scale for Children (WISC) among clinical and healthy samples (Bodin, Pardini, Burns, & Stevens, 2009; Borsuk, Watkins, & Canivez, 2006; Donders, 1996; C. R. Hale et al, 2014; Holcomb, Hardesty, Adams, & Ponder, 1987; Konold, Glutting, McDermott, Kush, & Watkins, 1999; Snow, Cohen, & Holliman, 1985; Vance, Wallbrown, & Blaha, 1978; Waxman & Casey, 2006).…”
mentioning
confidence: 74%
“…Distinct cognitive profiles characterized by specific weaknesses (in broad-based cognitive processing, executive functioning, verbal functioning, or nonverbal-visuospatial processing) were reported in previous cluster-analytic studies on the Wechsler Intelligence Scale for Children (WISC) among clinical and healthy samples (Bodin, Pardini, Burns, & Stevens, 2009; Borsuk, Watkins, & Canivez, 2006; Donders, 1996; C. R. Hale et al, 2014; Holcomb, Hardesty, Adams, & Ponder, 1987; Konold, Glutting, McDermott, Kush, & Watkins, 1999; Snow, Cohen, & Holliman, 1985; Vance, Wallbrown, & Blaha, 1978; Waxman & Casey, 2006).…”
mentioning
confidence: 74%
“…When it comes to predictive or incremental validity, research also indicates that profile level is the best predictor of educational outcomes, whereas profile shape adds minor incremental validity at best (Kahana et al, ; Watkins & Glutting, ). Further, Borsuk, Watkins, and Canivez () demonstrated that membership in WISC‐III subtest profile‐type groups was generally not stable over a 3‐year period (with the exception of two profiles, one of them containing a high frequency of learning‐disabled children). The low reliability of subtest scores in comparison to full‐scale IQ scores implies that profile analysis should not be used for classification purposes or for diagnostic labeling (Sattler & Saklofske, ).…”
Section: Interindividual Differences In Cognitive Abilities As Predicmentioning
confidence: 99%
“…However, the examination of intra-individual score patterns (i.e., the degree to which an examinee's IQ subtest scores match the invalid score profile) is problematic for numerous reasons. These types of score interpretations have been widely denounced primarily due to the lack of diagnostic utility for score profiles (Devena and Watkins 2012;Smith and Watkins 2004;Watkins et al 2002) and the temporal instability of subtest difference scores (Borsuk et al 2006;McDermott et al 1989aMcDermott et al , b, 1992Watkins and Smith 2013). Thus, the C-LIM was built on the shaky foundation of subtest score differences.…”
Section: Discussionmentioning
confidence: 98%